DEVELOPMENT OF METHODS OF PRE-COLUMNAR DERIVATIZATION OF GLUTATHIONES RECOVERED BY 4-METHOXY-2-NITROPHENYLISOTHIOTOCIONATE FOR DETERMINATION BY METHOD OF HIGH-EFFECTIVE LIQUID CHROMATOGRAPHY - K. A. Alexeeva; D. I. Pisarev; O. O. Novikov; A. Yu. Malyutina (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2018)
Nowadays the pharmacological role of glutathione in the therapy of carcinogenesis, neurodegenerative and ocular diseases, heart diseases, the immune system and aging of the organism is being actively investigated. Therefore, for the development of pharmaceutical medical forms on its basis, it is necessary to create an optimal analytical base. The aim of this study is to develop a methodology for the analysis of glutathione recovered by pre-columnar derivatization of 4-methoxy-2-nitrophenyl isothiocyanate. Materials and methods. Since glutathione does not have the necessary spectral characteristics for its direct analysis, a methodology for the determination of glutathione with the use of pre-columnar derivatization of 4-methoxy-2-nitrophenyl-isothiocyanate by reversed-phase high-performance chromatography (RP HPLC) has been developed on that basis. Detection of the resulting derivative has been carried out by absorption in UV light using a diode array detector. Results and discussion. In the course of the experiment described, chromatograms of a glulathione derivative with 4-methoxy-2-nitrophenyl isothiocyanate were obtained. This technique was also evaluated for the possibility of quantitative determination of glutathione. The sensitivity of the methods was 0.01% or 3.1*10-1 mol. The linear relationship between the analytical signal (peak area) and concentration was observed within the range of 0.01-0.08% and the correlation coefficient of 0.995. Conclusion. In the course of the studies, a methodology for the determination of glutathione has been developed with the use of pre-columnarderivatization of 4-methoxy-2-nitrophenyl-isothiocyanate by RP HPLC. In this case, the derivative is formed with the retention time of 22.3 minutes and the absorption maximum of 398 nm. This method also allows estimating the quantitative content of the object under study.